2022
DOI: 10.1519/jsc.0000000000004357
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Ratings of Perceived Exertion-Clamp Model to Examine the Effects of Joint Angle on the Time Course of Torque and Neuromuscular Responses During a Sustained, Isometric Forearm Flexion to Task Failure

Abstract: Application of the ratings of perceived exertion-clamp model to examine the effects of joint angle on the time course of torque and neuromuscular responses during a sustained, isometric forearm flexion to task failure. J Strength Cond Res 37(5): 1023-1033, 2023-The present study used the ratings of perceived exertion (RPE)-clamp model during a sustained, isometric forearm flexion task to failure to determine the effects of joint angle on torque and neuromuscular responses. Twelve college-aged women performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…In theory, differences in engaged muscle mass and torque production could result in differences in muscle oxygenation, adenosine triphosphate utilization, and metabolite buildup during the sustained isometric tasks (13). In addition, it has been hypothesized that fatigue-related differences in TTF between unilateral and bilateral tasks may be due to interhemispheric inhibition (1,18,36). Thus, these findings, in conjunction with those of Keller et al (18,19), suggested that the magnitude of performance fatigability following fatiguing isometric tasks anchored to RPE was dependent on the exercise mode and muscle group being examined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In theory, differences in engaged muscle mass and torque production could result in differences in muscle oxygenation, adenosine triphosphate utilization, and metabolite buildup during the sustained isometric tasks (13). In addition, it has been hypothesized that fatigue-related differences in TTF between unilateral and bilateral tasks may be due to interhemispheric inhibition (1,18,36). Thus, these findings, in conjunction with those of Keller et al (18,19), suggested that the magnitude of performance fatigability following fatiguing isometric tasks anchored to RPE was dependent on the exercise mode and muscle group being examined.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have examined the effects of joint angle (3), anchor scheme, and sex (36) on the torque and neuromuscular responses following fatiguing forearm flexion tasks anchored to RPE. Specifically, Arnett et al (3) examined the effects of joint angle on the MVIC and neuromuscular responses following fatiguing forearm flexion tasks anchored to RPE 5 8 in men and reported parallel decreases in pretest to posttest MVICs at elbow joint angles of 75°, 100°, and 125°, a decrease in EMG AMP at the elbow joint angle of 125°, and no changes in EMG MPF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested [14,15] that EMG AMP represents muscle excitation attributed to motor unit recruitment, firing rate, and/or synchronization. For example, previous studies have utilized EMG AMP to make inferences regarding fatigue-induced adjustments in motor unit activation strategies during and after sustained, isometric forearm flexion [7][8][9][10] and leg extension [11,16,17] tasks, with torque or force anchored to a constant RPE using the OMNI-RES (0-10) scale [18][19][20]. In addition, previous studies [21][22][23] have examined the ratio between normalized torque (or force) and normalized EMG AMP to estimate neuromuscular efficiency (NME: a measure of the level of excitation required to generate a given amount of torque).…”
Section: Introductionmentioning
confidence: 99%